An improved three-dimensional model for growth of oxide films induced by laser heating - Jiménez Pérez, J. L.; Sakanaka, P. H.; Algatti, M. A. [UNESP]; Mendoza-Alvarez, J. G.; Cruz Orea, A. (Elsevier, 2001)
In this paper we consider a three-dimensional heat diffusion model to explain the growth of oxide films which takes place when a laser beam is shined on and heats a metallic layer deposited on a glass substrate in a normal atmospheric environment. In particular, we apply this model to the experimental results obtained for the dependence of the oxide layer thickness on the laser density power for growth of TiO2 films grown on Ti-covered glass slides. We show that there is a very good agreement between the experimental results and the theoretical predictions from our proposed three-dimensional model, improving the results obtained with the one-dimensional heat diffusion model previously reported. Our theoretical results also show the occurrence of surface cooling between consecutive laser pulses, and that the oxide track surface profile closely follows the spatial laser profile indicating that heat diffusive effects can be neglected in the growth of oxide films by laser heating. © 2001 Elsevier Science B.V.
Keywords: Laser induced oxidation; Laser materials processing; Thin oxide films; Laser beam effects; Mathematical models; Oxides; Thermal diffusion; Thin films; Laser heating; Film growth